Hadith #22 - Sahih Muslim - Abu al-Walid أبو الوليد - بركة المجاشعي (Sahih Muslim)
I heard the messenger of Allah (ﷺ) say: Verily, al-Islam is founded on five (pillars): testifying the fact that there is no god but Allah, establishment of prayer, payment of Zakat, fast of Ramadan and Pilgrimage to the House.
Grade: Sahih

Hadith #1500 - Sahih Muslim - Abu al-Walid أبو الوليد - بركة المجاشعي (Sahih Muslim)
I heard ‘Abdullah b. al-Harith say: ‘Abdullah b. ‘Abbas addressed us on a rainy day, and the rest of the hadith is the same, but he made no mention of Jumu’a prayer, and added: He who did it (who commanded us to say prayer in our houses), i. e. the Messenger of Allah (ﷺ), is better than I.
Grade: Sahih